Insulin growth factor 2 (IGF2) as an emergent target in psychiatric and neurological disorders. Review. (December 2019) - Pardo, M.; Cheng, Y.; Sitbon, Y.H.; Lowell, J.A.; Grieco, S.F.; Worthen, R.J.; Desse, S.; Barreda-Diaz, A.
Graphical abstract: Highlights: The insulin growth factor 2 (IGF2) is abundantly expressed in the brain. Inappropriate IGF2 expression is implicated in a growing number of diseases. There is a correlation between IGF2 and memory performance in humans and animals. IGF2 is proposed as a new target to treat cognitive disabilities. We highlight the potential of external IGF2 administration as a pro-cognitive agent. Abstract: Insulin-like growth factor 2 (IGF2) is abundantly expressed in the central nervous system (CNS). Recent evidence highlights the role of IGF2 in the brain, sustained by data showing its alterations as a common feature across a variety of psychiatric and neurological disorders. Previous studies emphasize the potential role of IGF2 in psychiatric and neurological conditions as well as in memory impairments, targeting IGF2 as a pro-cognitive agent. New research on animal models supports that upcoming investigations should explore IGF2′s strong promising role as a memory enhancer. The lack of effective treatments for cognitive disturbances as a result of psychiatric diseases lead to further explore IGF2 as a promising target for the development of new pharmacology for the treatment of memory dysfunctions. In this review, we aim at gathering all recent relevant studies and findings on the role of IGF2 in the development of psychiatric diseases that occur with cognitive problems.